Hubungan Pengaruh Antara Kepemimpinan, Budaya Organisasi, Dan Kepuasan Kerja Terhadap Komitmen Organisasi Dosen - Syahid Suhandi Aziz (Universitas La Tansa Mashiro, 2014)
This study aimed to obtain empirical about the direct influence of organizational culture of leadership and job satisfaction on organizational commitment lecturer. In addition this study aimed to obtain empirically the direct impact of leadership and organizational culture on job satisfaction. This study used a survey method with path analysis techniques. The population in this study are all university professors Jayabaya much as 134 people. A sample taken from the population of 100 people by using Slovin formula. Based on the results of data analysis and discussion presented produce the following findings: (1) There is a direct effect of the positive leadership organizational culture and job satisfaction on organizational commitment; (2) There is a direct effect of the positive leadership and organizational culture on job satisfaction.